Effects of cytokinins and auxins on the micropropagation of a local grapevine (Vitis vinifera L.) cultivar, using nodal explants - Ali, Osman; Ali, Mohamed; Salama, Abdel Moneim (المجلة الزراعية; مجلد 11 عدد 2 (2013), 2013)
This study was conducted in the Plant Tissue Culture Unit of the Agricultural Research Corporation, Wad Medani, Sudan, during the years 2006- 2007. The objectives were to develop an in vitro technique for the propagation of a local cultivar of grapevine. The basal Murashige and Skoog medium was supplemented with benzylaminopurine (BAP) and kinetin both at concentrations of 0.0, 0.25, 0.5, 1.0, 2.0, 4.0, 6.0, and 8.0 mg/l. Isopentenyladenine (2iP) and BAP were also used at concentrations of 0.0, 1.0, 1.5, and 2.0 mg/l.  The interaction effects of indole acetic acid (IAA) at concentrations of 0.0, 0.25, 0.5 and 1.0 mg/l with BAP at 1.0 or 2.0 mg/l and indole butyric acid (IBA) at concentrations of 0.0, 0.1, 0.3, and 0.5 mg/l with 2iP at 1.0 or 2.0 mg/l were also tested. For in vitro rooting, plantlets were cultured on MS medium supplemented with different concentrations of NAA (0.0, 0.25, 0.5, and 1.0 mg/l). The best morphogenesis of shoots was achieved on MS medium supplemented with BAP at 1.0-1.5 mg/l. The morphogenetic response increased with time and the best response was attained after six weeks. Higher concentrations of BAP (2.0-8.0 mg/l) resulted in abnormal growth of plantlets. The combination of BAP with IAA did not improve shoot morphogenesis. The morphogenesis of the nodal explants was similar on kinetin and 2iP which resulted in a single shoot per explant. The combinations of 2iP at different concentrations with IBA did not improve shoot morphogenesis compared to 2iP alone. The best rooting of regenerated shoots of grapevine was achieved on MS medium supplemented with 0.25 and 0.5 mg/l NAA after four weeks. أجريت هذه الدراسة بوحدة زراعة الأنسجة النباتية بهيئة البحوث الزراعية بواد مدني، السودان، خلال الفترة 2006-2007 م. كان الهدف من هذه الدراسة إكثار السلالة البلدية لكرمه العنب عن طريق تقنية الإكثار النسيجي. أختبر أثر ثلاثة أنواع  من السيتوكينينات في وسط  موراشيجي واسكوق و هي بنزيل أمينوبيورين (BAP) و الكينيتين (kinetin ) بالتركيزات  0.0, 0.25 ،0.5 ،1.0، 2.0، 4.0، 6.0 و8.0 ملجم/لتر وآيزوبنتينيل أدنين (2iP)و BAP بالتركيزات 0.0 , 1.0 , 1.5 و2.0 ملجم/لتر . كما تم اختبار تداخلها مع بعض الاوكسينات مثل اندول حامض الخليك(IAA)   بالتركيزات     0.0, 0.25 ،0.5   و1.0 ملجم/لتر مع BAP  بتركيز 1.0 أو2.0 ملجم/لتر و اندول حامض البيوترك IBA) ) بالتركيزات 0.0 ,  0.1, 0.3 و0.5 ملجم/لتر مع   2iPبتركيز 1.0 أو2.0 ملجم/لتر . أختبر أثر منظم النمو نفثالين حامض الخليك (NAA ) بالتركيزات  0.0, 0.25،0.5   و1.0 ملجم/لتر علي تحفيز التجذير لنبتات سلالة العنب البلدية المنتجة نسيجيا.  اختلفت استجابة البراعم للإكثار النسيجي وذلك باختلاف منظم النمو ودرجة تركيزه. وكانت الاختلافات معنوية بين أنواع هذه المنظمات ودرجة تركيزها.  أفضل استجابة لنمو البراعم كانت علي وسط  موراشيجي واسكوق مضافا إليه BAP بتركيز 1.0 أو 1.5 ملجم/لتر مقارنة بمنظمات النمو الأخرى. كما إزدات أعداد النبتات النامية بزيادة فترة تحضين المنفصل النباتي المزروع حتى الأسبوع السادس. تسببت التركيزات العالية من BAP (2-8 ملجم/لتر) في إنتاج سيقان منتفخة و نمو غير طبيعي للأوراق. لم يؤدي تداخل IAA مع BAP إلي  زيادة عدد النبتات النامية علي المنفصل النباتي المزروع . منظمات النمو kinetin و2iP لم تظهر أي فروق معنوية ما بين  تركيزاتها المختلفة و كانت متساوية في عدد النبتات المنتجة وأعطت نبتة واحدة لكل منفصل نباتي. لم يحسن تداخل IBA مع 2iP في زيادة عدد النبتات النامية علي المنفصل النباتي المزروع.  أفضل استجابة لنمو الجذور كانت علي وسط  موراشيجي واسكوق مضافا إليهNAA  بتركيز 0.25 أو0.5 ملجم/لتر بعد أربعه أسابيع من الزراعة.